Form and substance in Singapore constitutional and administrative law - CHNG, Kenny (Institutional Knowledge at Singapore Management University, 2020)
This paper proposes to study constitutional and administrative law in Singapore through the lenses of Atiyah’s and Summers’ concepts of form and substance in order to discern fruitful avenues for the development of Singapore constitutional and administrative law. While the concepts of form and substance in the context of constitutional law are often associated with constitutional interpretation, they can also be fruitfully applied to other areas of constitutional and administrative law to shed light on the potential trajectories of Singapore law. The intent of this paper is to apply Atiyah’s and Summers’ concepts of form and substance to Singapore constitutional and administrative law to illustrate that beyond formalism in Singapore’s constitutional interpretation, formalism is an apt description for several key areas of Singapore constitutional and administrative law doctrine and reasoning, even to the extent of being formalistic. The paper will argue that formalism in legal reasoning obtains in several important constitutional and administrative law doctrines in Singapore – specifically, in the grounds of judicial review, ouster clause doctrine, and standing rules – and will evaluate the implications of these findings for the development of Singapore constitutional and administrative law.